2015
DOI: 10.3892/ol.2015.3456
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference for epidermal growth factor receptor enhances the radiosensitivity of esophageal squamous cell carcinoma cell line Eca109

Abstract: Abstract. The present study investigated the effects of small interfering RNAs (siRNAs) specific to the epidermal growth factor receptor (EGFR) gene, on the radiosensitivity of esophageal squamous cell carcinoma cells. EGFR gene siRNAs (EGFR-siRNA) were introduced into esophageal cancer Eca109 cells using Lipofectamine ® 2000. The EGFR messenger (m)RNA expression levels, EGFR protein expression and cell growth were assessed using reverse transcription-polymerase chain reaction analysis, western blot analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…AB01 and cAb showed similar binding capacity with EGFR, indicating that the change of α‐Gal does not affect the affinity of tested antibody. To further evaluate the effect on the proliferation of tumor cells, EGFR‐positive DiFi, A431, HCC827, FaDu, SW48 and Eca109 cells were chosen (Amann et al, 2005; Kol et al, 2017; Meira et al, 2009; Troiani et al, 2014; Yonesaka et al, 2019; Zhang et al, 2015). Results suggested that both AB01 and cAb significantly inhibited the proliferation of EGFR‐positive tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…AB01 and cAb showed similar binding capacity with EGFR, indicating that the change of α‐Gal does not affect the affinity of tested antibody. To further evaluate the effect on the proliferation of tumor cells, EGFR‐positive DiFi, A431, HCC827, FaDu, SW48 and Eca109 cells were chosen (Amann et al, 2005; Kol et al, 2017; Meira et al, 2009; Troiani et al, 2014; Yonesaka et al, 2019; Zhang et al, 2015). Results suggested that both AB01 and cAb significantly inhibited the proliferation of EGFR‐positive tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorothioate-modified ASOs (PS-ASOs) have been shown to downregulate EGFR via RNase H activation [ 30 ]. Short interfering RNAs downregulating the expression of epidermal growth factor receptors have been shown to enhance the chemosensitivity of well-established anticancer compounds (cisplatin, 5-fluorouracil, and docetaxel) [ 31 ] and radiosensitivity [ 32 ] in various cancer cells, including head and neck squamous cell carcinoma (HNSCCs). The anti-EGFR aptamer [ 33 ] induces selective apoptotic cell death and, upon structural optimization [the use of 2′- O -methyl (2′-OMe) units], its human serum stability and toxic potential are increased in breast cancer, liver cancer, and malignant glioblastoma cells [ 34 ].…”
Section: Introductionmentioning
confidence: 99%